Effectiveness of No-till Farming, Cover Cropping, and Crop Rotation in Improving the Sustainability of the Agricultural Sector in West Java - Loso Judijanto; Eddy Silamat (Westscience Press, 2024)
This study explores the effectiveness of three sustainable agriculture practices—No-till Farming, Cover Crops, and Crop Rotation—in enhancing the sustainability of the agricultural sector in West Java, Indonesia. Using structural equation modeling (SEM-PLS) to analyze survey data from 180 farmers, the study reveals positive relationships between each practice and sustainability outcomes. Cover Cropping emerges as particularly impactful, followed by No-till Farming and Crop Rotation. These findings emphasize the critical role of integrating these practices into agricultural policies and extension programs to bolster environmental resilience and economic viability across West Java.